Synthesis and antibacterial study of the ligand type Schiff base derived from amino acid [L- Phenylalanine] and its complexes with Co (II), Ni (II), Cu (II) and Zn (II) ions - Aziz, M. R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
L-Phenylalanine amino acid was condensed with 2-hydroxybezaldehyde to give the Schiff base sodium 2-(2-hydroxybenzylideneamino)-3-phenylpropanoate, which was used as a precursor [NaHL]. The precursor was reacted with 1,2-dichloroethane to give the Schiff base sodium 2,2'-(2,2'-(ethane-1,2diylbis(oxy))bis(2,1-phenylene))bis(methan-1-yl-1-ylidene)bis(azan1-yl-1-ylidene)bis(3-phenyl propanoate), which was used as a ligand [Na2L], in complexation with some metal (II) chloride MCl2, where [M= Co(II), Ni(II), Cu(II) and Zn(II)], to give [M(L)] complexes. The [Na2L] ligand and All complexes were characterized by spectroscopic methods, [FTIR, UV-Vis, atomic absorption], melting point, chloride content, conductivity and magnetic susceptibility measurements, as well as the Na2L ligand characterized by 1H NMR. The data, of these studies and measurements were important to suggest an octahedral geometry around Co(II), Ni(II), Cu(II) and Zn(II) ions. The synthesized ligand, along with its metal complexes, was screened for in vitro antibacterial activity against gram-positive bacteria like Staphylococcus aureus, and Acinetobacter baumannii. This study showed an effective inhibition of gram- positive bacteria.